Variation in Protein, Carbohydrate and Lipid Content in the Body Wall of Commercial Sea Cucumber Holothuria spinifera (Theel, 1886) in Relation to Reproductive Stages - Asha, P. S.; Muthiah, P. (Fishery Technology, 2018)
The dry body wall from sea cucumbers, is ‘beche-demer’,is an important item of trade in the developingcountries in the Indo-Pacific region. A study wasconducted to assess the variation in biochemicalconstituents of the body wall of commercial seacucumber Holothuria spinifera concerning the reproductivestages. The body wall of sea cucumbersbelong to eight reproductive stages were pooled anddried in hot air oven at 80oC for 48 h. Standardprocedures estimated the protein, total carbohydrateand total lipids. The mean values of proteins,carbohydrate and lipid content in the body wall ofH. spinifera were 17.2, 2.8 and 1.3%, respectively. Thehighest concentration of these organic constituentsduring the maturing stages, decline during the postspawningperiods indicating their role as the sourceof energy during gametogenesis. The one-wayANOVA on the differences in the mean protein,carbohydrate and lipid content in the body wall tothe reproductive stages indicated a high level ofsignificance (p